2008
DOI: 10.1159/000183731
|View full text |Cite
|
Sign up to set email alerts
|

Oncologists and Hepatitis B: A Survey to Determine Current Level of Awareness and Practice of Antiviral Prophylaxis to Prevent Reactivation

Abstract: Background/Aims: The risk of chronic hepatitis B virus reactivation under the influence of chemotherapy or immunosuppression is being increasingly recognized. However, many oncologists either have not observed this complication or are not aware of current recommendations for hepatitis B prophylaxis. Our aims were to determine the awareness of the reactivation risk and to understand the screening and prevention practices among oncologists. Methods: A questionnaire survey was administered to oncologists in the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 77 publications
0
22
0
1
Order By: Relevance
“…A recent survey, involving on-cologists in the US, highlighted a reduced prevalence of practitioner applied universal screening for HBV infection (14%) and that only 56% were aware of the availability of prophylactic therapy [75] . In addition, it is interesting to note that in its recent provisional clinical opinion on chronic HBV infection screening in patients receiving CHT, the American Society of Clinical Oncology states that there is insufficient evidence of the net benefits and harms of routine HBV screening in these individuals.…”
Section: Managementmentioning
confidence: 99%
“…A recent survey, involving on-cologists in the US, highlighted a reduced prevalence of practitioner applied universal screening for HBV infection (14%) and that only 56% were aware of the availability of prophylactic therapy [75] . In addition, it is interesting to note that in its recent provisional clinical opinion on chronic HBV infection screening in patients receiving CHT, the American Society of Clinical Oncology states that there is insufficient evidence of the net benefits and harms of routine HBV screening in these individuals.…”
Section: Managementmentioning
confidence: 99%
“…While screening for hepatitis B is recommended by hepatology society guidelines [119] and TNF-alpha antagonists package labeling, it is performed infrequently. Our group has reported inadequate screening for hepatitis B in oncology and rheumatology patients receiving TNF-alpha antagonist therapy [120,121] . It is recommended that efforts be made to screen all patients universally for hepatitis B prior to initiating therapy with biologics [122,123] .…”
Section: Hepatic Injury From Reactivation Of Viral Hepatitis On Ibd Tmentioning
confidence: 99%
“…However, among specialists who screen, only 46% order HBcAb as part of the screening workup [70••]. Another study [72] conducted among oncologists revealed that 20% were not aware of HBV reactivation and only 56% were aware of need for prophylactic antiviral therapy. Only 38% of oncologists in the study screened patients for HBV prior to chemotherapy.…”
Section: Awarenessmentioning
confidence: 99%